Hubungan Dukungan Keluarga dan Kepatuhan Diet Hipertensi Dengan Derajat Hipertensi pada Pasien Dewasa di Puskesmas X: The Relationship Between Family Support and Hypertension Diet Compliance with the Degree of Hypertension in Adult Patients at Community Health Center X - Tommy Wowor; Retno Widowati; Mia Atlantic; Niken Rima Fadilla (Journal of Nursing Education and Practice, 2026)
Introduction: Hypertension is a non-communicable disease with a high prevalence in Indonesia. The prevalence of hypertension among individuals aged 18 years and older increased from 25.8% in 2013 to 34.1% in 2018. Effective hypertension management requires adherence to a hypertension diet; however, dietary compliance remains low and is influenced by various factors, including family support. Family support plays an important role in encouraging healthy behaviors and improving adherence to dietary recommendations among patients with hypertension.Objectives: To determine the relationship between family support and adherence to a hypertension diet with the degree of hypertension among adult patients in the working area of the Cilodong Depok Community Health Center.Method: This study employed a quantitative research design with a cross-sectional approach. The study was conducted at the Cilodong Community Health Center involving 91 adult patients with hypertension selected through accidental sampling based on predetermined inclusion criteria. Data were collected using the Family Support Scale (FSS) questionnaire, a hypertension diet adherence questionnaire, and blood pressure measurements using a sphygmomanometer. Data were analyzed using univariate and bivariate analyses with the Chi-Square statistical test.Result: The results showed a significant relationship between family support and adherence to a hypertension diet among adult patients with hypertension (p < 0.05). Respondents who received good family support were 23.131 times more likely to adhere to a hypertension diet compared to those with poor family support (OR = 23.131). Furthermore, family support and diet adherence were significantly associated with the degree of hypertension.Conclusion: There is a significant relationship between family support and adherence to a hypertension diet with the degree of hypertension among adult patients in the working area of the Cilodong Depok Community Health Center. Strengthening family involvement may improve dietary adherence and contribute to better hypertension control.